We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
-4
110
1
avatar+25 

-2x^2=-(5x+4) solve using the quadratic equation.

 May 31, 2019
 #1
avatar+8756 
+3

-2x2  =  -(5x + 4)

                               Distribute  -1  to the terms in parenthesees.

-2x2  =  -5x - 4

                               Add  2x2  to both sides of the equation.

0  =  2x2 - 5x - 4

 

2x2 - 5x - 4  =  0

 

2x2 + -5x + -4  =  0

 

This is a quadratic equation. We can use the quadratic formula to solve for  x .

 

The quadratic formula says that....

 

If     ax2 + bx + c  =  0     then     \( x=\frac{-\mathbf{\color{blue}b}\pm\sqrt{\mathbf{\color{blue}b}^2-4\mathbf{\color{Magenta}a}\mathbf{\color{Green}c}}}{2\mathbf{\color{Magenta}a}}\)

 

So...

 

Since     2x2 + -5x + -4  =  0     then     \( x=\frac{-(\mathbf{\color{blue}-5})\pm\sqrt{\mathbf{(\color{blue}-5})^2-4(\mathbf{\color{Magenta}2})(\mathbf{\color{Green}-4})}}{2(\mathbf{\color{Magenta}2})}\)

 

\(x=\frac{-(-5)\pm\sqrt{(-5)^2-4(2)(-4)}}{2(2)}\\~\\ x=\frac{5\pm\sqrt{25+32}}{4}\\~\\ x=\frac{5\pm\sqrt{57}}{4}\\~\\ x=\frac{5+\sqrt{57}}{4}\qquad\text{or}\qquad x=\frac{5-\sqrt{57}}{4}\)

.
 May 31, 2019

35 Online Users

avatar